PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS VIDEO ANIMASI UNTUK MENINGKATKAN KETERAMPILAN LITERASI DIGITAL PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA DI KELAS II SDN NGERUKEMAN - Rendra Bangkitjaya; Heru Purnomo (STKIP Subang, 2026)
This study used the RnD (Research and Development) research method that refers to the ADDIE development model. The study was conducted at SDN Ngrukeman with limited trial subjects of 8 second-grade students and field trial subjects of 19 second-grade students. Data collection instruments used were observation, interviews, questionnaires, and tests. Data analysis techniques used qualitative and descriptive quantitative data analysis. The results of this study produced a product in the form of interactive animated video learning media to improve students' digital literacy skills. The feasibility results were obtained from the validation of media experts and material experts who obtained different results, namely media experts got 90.6% and material experts got a percentage of 89.3% in the very feasible category. Media practicality data was obtained from the results of the teacher response questionnaire with a percentage of 96% and a student response questionnaire of 91.05% including the very practical category. Media effectiveness test data was obtained from the results of the pretest and posttest which obtained an average pretest score of 56.2% with a low category and a posttest of 85.1% in the very good category, there was an increase between the pretest and posttest results of 28.9% which means the media can improve students' digital literacy skills. Based on the results of the study, it can be concluded that interactive learning media based on animated videos is very feasible, practical and effective for use in learning.